Persistent emotional stress, fatigue and impaired neurocognitive function in recovered COVID-19 patients: a longitudinal prospective study. (1st June 2022) - Rogiers, A.; Launay, S.; Duque, G.; Soukias, E.; Van Eycken, S.; Besse-Hammer, T.; Sanchez-Rodriguez, D.; Chalon, M.; Gazagne, M.-D.; Maillart, E.; Benoit, F.; Surquin, M.; et al.
Abstract : Introduction: Several surveys report that post-COVID-19 patients (pts) could be at risk of persistent emotional distress, fatigue and impaired neurocognitive function (NCF). Objectives: The aim was to assess emotional distress, fatigue and NCF in order to provide adequate care. Methods: Patients with persistent physical or mental symptoms, at least 8 weeks post-COVID-19, were eligible for this ongoing prospective longitudinal single center trial. Data on depression, anxiety, cognition, post-traumatic stress symptoms (PTSS) and fatigue were collected using 4 validated questionnaires at study entry (T0) and at 6 months (T1). Results: Ninety-three pts were recruited between November 2020-March 2021. Test results from 64 eligible pts (15 male pts) were analyzed at T0; 63 pts (98%) were treated in outpatient settings. Median age was 47 years [range 27-75]). Median time since COVID-19 was 29 weeks [range 8-53]. Twenty-two pts (34%) had a history of psychiatric disorders. According to the Hospital Anxiety Depression Scale (HADS), 44 pts (73%) reported anxiety symptoms and 26 pts (41%) reported depressive symptoms; 48 pts (69%) reported cognitive complaints according to the Cognitive Failure Questionnaire and 29 pts (45%) suffered from PTSS, according to the Post-Traumatic Stress Disorder Checklist-Civilian Version (PCL-C). Fifty-five pts (86%) had an elevated score on the Fatigue Severity Scale, indicating severe fatigue. Twenty-seven pts (42%) were still on sick leaf. Diminished social support and psychiatric history were predictive factors for neurocognitive dysfunction and PTSS. Conclusions: A majority of patients who recovered physically from COVID-19, are at risk for suffering from persistent anxiety, PTSS and neurocognitive dysfunction. Disclosure: No significant relationships.